2023
DOI: 10.3390/en16186441
|View full text |Cite
|
Sign up to set email alerts
|

Methane Pyrolysis with the Use of Plasma: Review of Plasma Reactors and Process Products

Mateusz Wnukowski

Abstract: With the increasing role of hydrogen in the global market, new ways of hydrogen production are being sought and investigated. One of the possible solutions might be the plasma pyrolysis of methane. This approach provides not only the desired hydrogen, but also valuable carbon-containing products, e.g., carbon black of C2 compounds. This review gathers information from the last 20 years on different reactors that were investigated in the context of methane pyrolysis, emphasizing the different products that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 119 publications
0
7
0
Order By: Relevance
“…12, 58 The most well-known mechanism was proposed by Chen et al 58,59 with the reactions are shown in reactions 7−10 and the net overall reaction in reaction 11 will mainly correspond to hydrogen and solid carbon, as shown in reaction 11, if the time and temperature increase. 34 Methane is known for its thermodynamic stability owing to the strong carbon−hydrogen (C−H) bonds within its molecular structure. Breaking these bonds during MP requires overcoming a considerable energy barrier, which results in an endothermic process.…”
Section: Hydrogen From Methane Pyrolysismentioning
confidence: 99%
See 3 more Smart Citations
“…12, 58 The most well-known mechanism was proposed by Chen et al 58,59 with the reactions are shown in reactions 7−10 and the net overall reaction in reaction 11 will mainly correspond to hydrogen and solid carbon, as shown in reaction 11, if the time and temperature increase. 34 Methane is known for its thermodynamic stability owing to the strong carbon−hydrogen (C−H) bonds within its molecular structure. Breaking these bonds during MP requires overcoming a considerable energy barrier, which results in an endothermic process.…”
Section: Hydrogen From Methane Pyrolysismentioning
confidence: 99%
“…56 Table 5. Comparative Analysis of Different Reactor Types for Methane Pyrolysis characteristics fixed-bed reactor 119−121 moving bed and fluidized bed reactor 11,30,102,122 liquid metal bubble column reactor 19,71,91,123 plasma reactor 34,35,111,124,125 working principle methane gas passes through a fixed bed of catalyst particles methane flows through a bed of moving particles, enhancing contact with the catalyst methane bubbles through a column of liquid metal, decomposing into hydrogen and solid carbon currently limited because of small to medium scale and high energy requirements cost moderate; catalyst cost is significant higher than fixed-bed due to complexity and moving parts high initial cost but lower operational cost due to catalyst durability relatively high due to energy consumption and maintenance advantages simple design, easy to operate. improved heat and mass transfer, longer catalyst life high conversion rates, efficient heat management high conversion rates due to high temperature and energy input limitations catalyst deactivation due to coking is a major issue more complex design and operation, higher cost high initial setup cost, handling of liquid metals electrode erosion, high operational cost, complex maintenance The techno-economic aspects of MP are complex and depend on various factors, such as the type of reactor and catalyst used, the cost of natural gas, and the type, amount, and price of solid carbon produced.…”
Section: Techno-economics Of Methane Pyrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…During this process, various harmful substances such as carbon dioxide are emitted [22]. Consequently, if carbon black derived from plasma-based methane pyrolysis, which is simpler than the furnace black method, is utilized as a high -value-added material, it can lead to substantial energy cost sav- ings [23].…”
Section: Introductionmentioning
confidence: 99%